Values of Religious Moderation in the Thought of Indonesian Ulemas: Study of Islamic History and Education Literature - Sahroni, Sahroni; Tajam, Muri; Yana, Hawwin Huda (FALASIFA : Jurnal Studi Keislaman, 2025)
This research examines the idea of religious moderation in the teachings of Nusantara scholars, which is very important in creating social harmony in diverse Indonesia. In the midst of increasing religious extremism, the moderation taught by Nusantara scholars is very relevant to be studied more deeply. This study aims to analyze the values of religious moderation in the thought of Nusantara scholars and its relevance in the current social context and Islamic education. The method used is a literature study with a qualitative approach, analyzing classical texts and the thoughts of scholars, and seeing how they are applied today. The results show that religious moderation developed by Nusantara scholars, such as Wali Songo and Hasyim Asy'ari, has a strong foundation in creating an inclusive and tolerant society. The research also shows the importance of applying the values of religious moderation in Islamic education and the wise use of digital technology in disseminating these teachings. This research opens up opportunities for further research on the role of Nusantara scholars in shaping a more harmonious society.